2002
DOI: 10.1203/00006450-200212000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Photooxidation of Parenteral Multivitamins Induces Hepatic Steatosis in a Neonatal Guinea Pig Model of Intravenous Nutrition

Abstract: Photooxidation of multivitamin solutions results in the generation of peroxides. Because peroxides are associated with hepatic steatosis and fibrosis as well as cholestasis, we questioned whether multivitamins are implicated in hepatic complications of parenteral nutrition. Guinea pig pups were assigned to groups receiving intravenously either total parenteral nutrition, photo-protected or not, or a control solution (5% dextrose + 0.45% NaCl) supplemented with either a) multivitamins; b) photo-protected multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 42 publications
4
36
0
4
Order By: Relevance
“…Faced with problems linked to the immature antioxidant defenses of premature newborn infants, clinicians might be tempted to increase the infusion of multivitamin solutions because they contain antioxidant vitamins that have documented antiradical properties (18,19 ). However, this process could increase the infusion of these byproducts of vitamin C. The present study confirms the findings of Silvers et al (13 ) that the concentration of ascorbic acid decreases within minutes after exposure to light (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Faced with problems linked to the immature antioxidant defenses of premature newborn infants, clinicians might be tempted to increase the infusion of multivitamin solutions because they contain antioxidant vitamins that have documented antiradical properties (18,19 ). However, this process could increase the infusion of these byproducts of vitamin C. The present study confirms the findings of Silvers et al (13 ) that the concentration of ascorbic acid decreases within minutes after exposure to light (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…3 Many of the proposed risk factors for PNAC have been recently reviewed, 4,5 and include low birth weight, prematurity, duration of PN, lack of enteral intake, sepsis, enzyme deficiencies, genetic causes, quantity or quality of amino-acid intake, excess of nonprotein caloric intake, and trace mineral toxicity. Male gender, 6 perinatal depression or shock, 7 and more recently, phototoxicity of parenteral multivitamin supplements, 8 and toxicity from plant phytosterols 9 have also been implicated as potential risk factors for PNAC. Although several of these risk factors are unavoidable, research is still needed to define the optimal parenteral amino-acid solution for pediatric and neonatal patients, 10 one that would allow normal growth and development, result in normal serum aminoacid levels, and cause a minimum of unwanted side effects, such as cholestasis.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress (1, 9 -11 ) and products derived from photooxidation of amino acids (9,12 ) have also been proposed. In a previous study (13 ), we reported that in a neonatal animal model on TPN, fatty liver was associated with the infusion of parenteral multivitamin preparations (MVPs), a component of TPN. We suspected an ingredient of MVP that might be generated during light exposure.…”
mentioning
confidence: 99%